Management Earnings Forecasts and Value of Analyst Forecast Revisions - Kim, Yongtae; Song, Minsup (Management Science, 2015)
This study examines the stock-price reactions to analyst forecast revisions around earnings announcements to test whether preannouncement forecasts reflect analysts' private information or piggybacking on confounding events and news. We find that management earnings forecasts influence the timing and precision of analyst forecasts. More importantly, evidence suggests that prior studies' finding of weaker (stronger) stock-price responses to forecast revisions in the period immediately after (before) the prior-quarter earnings announcement disappears once management earnings forecasts are controlled for. To the extent that management earnings forecasts are public disclosures, our results suggest that the importance of analysts' information discovery role documented in prior studies is likely to be overstated. This paper was accepted by Wei Jiang, finance.